1998
DOI: 10.1111/j.1600-0773.1998.tb01418.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 Specificity of Metabolism and Interactions of Oxybutynin in Human Liver Microsomes

Abstract: Ahstyuct; Oxybutynin has an extensive first pass metabolism after oral administration. the main active metabolite being N-desethyloxybutynin. The purpose of this study was to investigate the CYP isoform specificity of oxybutynin N-deethylation and possible interactions. Oxybutynin N-deethylation in human liver microsomes in vifro was potently inhibited by ketoconazole (ICso 4.5 pM), less and variably by itraconazole and not by quinidine or several other reference inhibitors, suggesting that CYP3A enzymes are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Such an observation is supported by the ;2-fold increase in fluconazole K i with CYP3A5 expresser (versus CYP3A5 nonexpresser) HLM (Isoherranen et al, 2008). There are reports that itraconazole (ITZ) is rCYP3A4 selective with substrates such as oxybutynin and midazolam (MDZ) (Lukkari et al, 1998;Yamazaki et al, 2010). The latter authors reported a K i ratio of ;30 (rCYP3A5/rCYP3A4) as well as a K i ratio of ;2 in HLMs (CYP3A5 expressers versus nonexpressers).…”
Section: Introductionsupporting
confidence: 49%
“…Such an observation is supported by the ;2-fold increase in fluconazole K i with CYP3A5 expresser (versus CYP3A5 nonexpresser) HLM (Isoherranen et al, 2008). There are reports that itraconazole (ITZ) is rCYP3A4 selective with substrates such as oxybutynin and midazolam (MDZ) (Lukkari et al, 1998;Yamazaki et al, 2010). The latter authors reported a K i ratio of ;30 (rCYP3A5/rCYP3A4) as well as a K i ratio of ;2 in HLMs (CYP3A5 expressers versus nonexpressers).…”
Section: Introductionsupporting
confidence: 49%
“…The patient had been treated with diazepam immediately before death; no other medications were given. The liver samples were frozen in liquid nitrogen and stored at -80" until preparation of microsomes as described previously (Lukkari et al 1998). The microsomal protein concentration of the preparation used was 16.2 mg ml-'.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies demonstrated that Oxybutynin is metabolized by oxidation via cytochrome P450 (CYP3A subfamily), 18,19 which also catalyzes Carbamazepine and influences activities of this and other cytochromes in human liver microsomes. 20 The exact pathway of Dantrolene metabolism is unknown, but some reports suggest that Dantrolene decreases the activity of cytochrome P450 21 and that this inhibition is dose dependent.…”
Section: Discussionmentioning
confidence: 99%